Biology of ICT-based communication paradigm - Darmawan, D. (2011)
A simple phenomenon and sometimes forgotten by all educators, both of basic and higher higher education levels, whereas this phenomenon is the basis of the meaningfulness of a Learning Interaction. In the context of Communication, the phenomenon should be developed, applied, and analyzed by all educators, especially to create the instructional communication quality in every lesson. This paper discussed about the analysis of biological communications technology-based on biological analysis for learners in a learning process. In-depth analysis focused on the effect of the learning stimulus packaged in the form of computer-based instruction (CBI). Results of analysis and verification Learning Interaction phenomena, taking into account the great power of Allah SWT, is the Brain Action. The result gave birth to a new paradigm where specifically focused as a basis for policy thinking designers, developers, implementers and assessors an innovative learning. On the other hand, the results of this research gave birth to a new branch of science in the field of communication learning, that is the "Biology of Communication.